Caste-specific gene expression underlying the differential adult brain development in the honeybee Apis mellifera - de Paula Junior, D. E. (2021)
Apis mellifera adult workers feature more developed key brain regions than queens, which allows them to cope with the broad range of duties they need to perform in a colony. However, at the end of larval development, the brain of queens is largely more developed than that of workers. Major morphogenetic changes take place after metamorphosis that shift caste-specific brain development. Here, we tested the hypothesis that this phenomenon is hormonally governed and involves differential gene expression. Our molecular screening approach revealed a set of differentially expressed genes in Pp (first pharate-adult phase) brains between castes mainly coding for tissue remodelling and energy-converting proteins (e.g. hex 70a and ATPsynβ). An in-depth qPCR analysis of the transcriptional behaviour during pupal and pharate-adult developmental stage in both castes and in response to artificially augmented hormone titres of 18 genes/variants revealed that: i. subtle differences in hormone titres between castes might be responsible for the differential expression of the EcR and insulin/insulin-like signalling (IIS) pathway genes; ii. the morphogenetic activity of the IIS in brain development must be mediated by ILP-2, iii. which together with the tum, mnb and caspase system, can constitute the molecular effectors of the caste-specific opposing brain developmental trajectories.